Venous Thromboembolism in Orthopaedic Trauma. Issue 1 (January 2015) - Scolaro, John A.; Taylor, Ryan Metri; Wigner, Nathan A.
Abstract : Patients who sustain orthopaedic trauma are at risk for developing deep venous thrombosis and symptomatic pulmonary emboli. The prevention of venous thromboembolism has moved to the forefront of patient safety initiatives, resulting in the formation of various guidelines to assist the practitioner. Recommendations for venous thromboembolism prophylaxis in the orthopaedic trauma patient exist, but there is insufficient evidence in the literature to make strong recommendations regarding type and duration of prophylaxis. The associated morbidity of chemical anticoagulants used in the orthopaedic trauma patient must also be taken into consideration, specifically the increased risk of bleeding. Mechanical prophylaxis is used in place of, or in addition to, these medications in certain situations. New, potentially superior anticoagulants have been developed but are still understudied. Larger studies are needed to further define the type and duration of deep venous thrombosis prophylaxis in the orthopaedic trauma patient.